The Constitutional Court's Position as the Guardian of the Constitution: Between Independence and Political Intervention - Narwadan, Theresia Nolda Agnes; Mulyana, Yusep; Fauzan, Fauzan (PT. Hafasy Dwi Nawasena, 2025)
This study discusses the position of the Constitutional Court (MK) as the guardian of the constitution in facing the dilemma between independence and political intervention. Using the Systematic Literature Review (SLR) approach by searching 915 articles, this study succeeded in identifying 50 relevant articles which were then analyzed thematically. The results of the study show that the independence of the Constitutional Court is still vulnerable to political pressure, both through the mechanism of appointment of judges, revisions of the Constitutional Court Law, and the practice of non-procedural dismissal. This phenomenon is in line with the global pattern of democratic backsliding that has also occurred in other countries such as Hungary, Turkey, and Poland, where the constitutional judiciary is weakened through court-packing strategies and legislative control. The main findings of the study confirm that controversial decisions, such as Decision No. 90/PUU-XXI/2023, have a direct impact on the legitimacy of the Constitutional Court in the eyes of the public and cause debates regarding ethics and conflicts of interest. The recommendations offered include reforming the merit-based selection mechanism of judges, protecting the term of office from political interference, and strengthening external oversight based on public participation. Thus, this study emphasizes the importance of adaptive and transparent institutional design so that the Constitutional Court is able to carry out its optimal role as the guardian of the constitution in maintaining the rule of law and democratic integrity in Indonesia.